KAJIAN PENAMBAHAN ABU CANGKANG SAWIT TERHADAP KUAT TEKAN BATA MERAH - Deltiana Rosalia; Elhusna Elhusna; Agustin Gunawan (Inersia: Jurnal Teknik Sipil, 2019)
This study was aimed to determine the effect of adding palm shell ash to the red brick  compressive strength. Palm shell ash is pozzolanic and contains about 60% silica and when it is mixed with clay bricks, the strength become stronger. This study used two methods of treatment  of the palm shell ash, oven and unoven. Bricks was made in this study using SII-0021-1978, while the red brick compressive strength was tested in this study using SNI 03-4164-1996. TheSpecimens were 146 cubes with a size of 5 cm on each side. The Variations in ash were used as an added ingredient of red brick at 0%, 4,3%, 8,6%, 12,9%, 17,2% and 21,5%. Specimens molded and dried for about 1 week and then burned in a red brick factory. The test results showed the addition of oven and unoven palm shell ash was increased the compressive strength of red brick. The addition of unoven palm shell ash was decreased the water absorption of the red brick and made the red brick lighter. The Lightest weight of the brick occurred in 8,6% of unoven palm shell ash was 12.96% of the normal one. The bigest compressive strength occured in 4,3% oven palm shell ash that was 112.82% of the normal red bricks. The smallest water absorption occurs in 8,6% of unoven palm shell ash was 18.07% of the normal red bricks.